Pediatric Blood Lead Levels Within New York City Public Versus Private Housing, 2003–2017 - Chiofalo, Jacqueline M. (Am J Public Health, 2019)
Objectives. To compare blood lead levels (BLLs) among children residing in public and private housing in New York City and examine the implications for lead identification and remediation policies. Methods. We examined electronic medical records for BLLs among 4693 children receiving care at a multisite Federally Qualified Health Center during 2003 to 2017. We plotted home addresses against city housing data to assess BLL differences between children living in public housing and private housing. Results. Only 0.25% of children residing in public housing had BLLs exceeding the upper reference limit of 5 micrograms per deciliter, as compared with 2.76% of children residing in private housing. After adjustment for age, gender, and race/ethnicity, public housing was associated with 92% lower odds of having a BLL of 5 micrograms per deciliter or above (odds ratio [OR] = 0.08; 95% confidence interval [CI] = 0.02, 0.33; P = .001). Decreases in BLLs were observed in both public and private housing over time. Conclusions. Children living in public housing in New York City were significantly less likely to have elevated BLLs than were children living in private housing. Decreases in BLLs over time were likely a result of lead reduction legislation.